Seasonality influences key physiological components contributing to Culex pipiens vector competence - Field, Eleanor N.; Smith, Ryan C. (Frontiers in Insect Science, 2023)
Mosquitoes are the most important animal vector of disease on the planet, transmitting a variety of pathogens of both medical and veterinary importance. Mosquito-borne diseases display distinct seasonal patterns driven by both environmental and biological variables. However, an important, yet unexplored component of these patterns is the potential for seasonal influences on mosquito physiology that may ultimately influence vector competence. To address this question, we selected Culex pipiens, a primary vector of West Nile virus (WNV) in the temperate United States, to examine the seasonal impacts on mosquito physiology by examining known immune and bacterial components implicated in mosquito arbovirus infection. Semi-field experiments were performed under the context of spring, summer, and late-summer conditions, respectively corresponding to periods of historically low, medium, and high-intensity periods of WNV transmission. Through these experiments, we observe differences in the expression of immune genes and RNAi pathway components, as well as changes in the distribution and abundance of Wolbachia in the mosquito across seasonal cohorts. Together, these findings support that seasonal changes significantly influence mosquito physiology and components of the mosquito microbiome, suggesting that seasonality may impact mosquito susceptibility to pathogen infection which could account for the temporal patterns in mosquito-borne disease transmission.